WORK – LIFE BALANCE CRETEAS WELL-BEING THROUGH SUSTAINABLE HUMAN RESOURCE MANAGEMENT AT ET CETTERA - Nuratika Pasaribu; Rizka Putri; Lifani Labolo; Irwan Nopian Sinaga (CV Naskah Aceh, 2025)
This study aims to thoroughly examine how sustainable human resource management (HRM) practices are implemented at the et Cetera fashion boutique located in Medan Centre Point Mall, and to what extent these practices influence work-life balance and employee well-being. Using a descriptive qualitative approach, data were collected through in-depth interviews, direct observation, and review of internal company documents. The study's findings reveal that, although working hours are generally within normal limits, increased workloads during certain periods and the lack of flexibility and compensation present challenges in achieving work-life balance. Moreover, although social relationships among employees are positive, the reward system and training programs are not yet systematically managed. Based on these findings, it is recommended that et Cetera develop more comprehensive and sustainable HRM policies, including flexible working arrangements, fair incentive systems, and support for employees' physical and psychological well-being. These measures are expected to improve employee loyalty and productivity while enhancing business resilience in the face of industry dynamics.